Fractional Coprecipitation of Drugs and Natural Extracts with Zinc Hydroxide - Andrea Franzese; Luca Regazzoni (Molecules)
Zinc hydroxide has been reported as an effective precipitating reagent for removing proteins in biological samples. This procedure is quite effective for removing interfering proteins before the chromatographic separation of small organic compounds. However, preliminary data suggested that also some small molecules could precipitate together with proteins and zinc hydroxide. Therefore, herein it is reported a study on a panel of drugs having different chemical structures. The results suggest that the common trait of organic molecules coprecipitating with zinc hydroxide is to have acidic groups, while neutral or basic molecules are not affected by zinc hydroxide precipitation. Such observations were consistent with some analyses conducted on hydroalcoholic extracts prepared from natural edible materials such as green tea. In such matrices, a quantitative coprecipitation of polyphenols was obtained upon inducing the precipitation of zinc hydroxide, while alkaloids such as caffeine remained selectively isolated in the supernatants. Interestingly, the compounds coprecipitated with zinc hydroxide can be easily and quantitatively recovered as well, just by redissolving the precipitate. These findings open potential applications for the isolation of specific classes of compounds from crude natural extracts and for the use of zinc hydroxide to remove interfering compounds before chromatographic analyses.